New methods for dynamically substructured system testing of a railway car pantograph. (February 2023) - Kobayashi, Shigeyuki; Koyama, Tatsuya; Harada, Satoshi; Stoten, David P
This study proposes new pantograph testing methods for railway pantograph/overhead catenary systems (OCS), based upon substructured testing consisting of a physical pantograph and a numerical OCS model. Hence, this work builds upon a previously presented work, (using the dynamically substructured system approach developed by Stoten and Hyde), which was conducted on a relatively simple mechanical structure in the Automatic Control and Test Laboratory (ACTLab), University of Bristol, UK. In this current paper, the dynamically substructured system (DSS) testing method is applied to a real shinkansen pantograph, using various actuator/DSS configurations that have been implemented at the Railway Technical Research Institute, Tokyo, Japan. In the first of these tests, a conventional servohydraulic actuated rig is used to represent phenomena due to the dropper-passing frequency. Resulting DSS test data are compared with those generated by a numerical simulation of the emulated system, i.e. the system to be represented by the DSS experimentation. Then, in the second set of investigations, the DSS method is used in conjunction with a new 'rotational disc' test rig that is arranged to be in dynamic interaction with the shinkansen pantograph contact head. This novel experimental system enables the investigation of dynamic interactions between the overhead catenary system contact wire and the pantograph head, due to span-passing. Again, results from this experimental investigation are compared with those generated by a purely numerical simulation of the emulated system.